Status of Tree Volume Calculation and Development of Allometric Equations in Pakistan - Nizami, Syed Moazzam; Nasir, Syed Mahmood (Indian Forester, 2016)
This paper reviews and analyses the biomass and volume allometric models that have been developed for various tree species in forest ecosystem types in Pakistan. The mathematical form of the allometric model, the associated statistical parameters, as well as information about the size (tree diameter and height) and the number of the sample trees used to develop models were collected from various sources published in scientific (both international and national) journals, student thesis and conference presentations. The total number of allometric models that have been reviewed in this paper are 18 consisting of 16 models for estimating biomass of tree components and 2 models for calculating stem volume. The spatial distribution analysis showed that these models have been prepared for dominant species of sub-tropical and coniferous sub-alpine forest ecosystems of Pakistan. These species include Acacia modesta (Phulai), Olea ferruginea (Kahu), Pinus roxburghii (Chir) and Betula uitlis (Birch). In biomass models, both above and below ground biomass have been considered. Besides information on model distribution, data coverage, this paper analyses the gaps and proposes strategies to fill the gaps. The collected information on the models provides a basic tool for estimation of forest biomass relevant to its ecosystem. This information also provides input to support the national forest carbon accounting for REDD+.